French socialists before Marx : workers, women and the social question in France - Pilbeam, Pamela M., 1941- (McGill-Queen's University Press, 2000)
French socialism traces its origins to the revolutionary communist Gracchus Babeuf (1760-1797) and for a time during the Second Republic socialists such as Louis Blanc, Etienne Canet, Victor Considérant, Jeanne Deroin, Pauline Roland, Blanqui, and Raspail occupied a prominent place in the attempt to create a reforming social democracy. For Karl Marx, and the dominant academic historians of twentieth-century France who took up his thesis, the early French socialists were worthy only of faint praise or scorn, yet the French parliamentary socialist groups that emerged in the 1880s can be understood only through reference to their predecessors. French Socialists before Marx identifies the major issues for French socialists between 1796 and the 1850s - revolution, religion, education, the status of women, association, and work. Pilbeam demonstrates that the socialists' answer to emerging capitalist competition and social conflict was association, while conservatives, in contrast, defended a liberal economy and united to persecute, prosecute, and deport socialists. French Socialists before Marx fills a significant void in socialist studies, enhancing our understanding of nineteenth-century social thought and strategies. It will be invaluable reading for students of history, politics, gender, French, and European studies.